E-Commerce Buy-Purchase Transactions Methods For Resoluting Consumer Disputes Relating To Items That Do Not Comply With The Agreement - Bayu Aji, Muhammad Taufan; Purwaningsih, Prihatini; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2024)
The process for handling customer complaints in online sales and purchases of goods that are not in compliance with such agreements are covered in this script. There are still gaps in the legal protection provided by these laws, although they have been set up to regulate the technical aspects of electronic commerce because parties who break agreements and trade online often cause damage to buyers and sellers in electronic transactions. One of the parties judged that the resolution would still be to their detriment. To the extent to which a law regulates and prosecutors are examined in this study use the normative-legal research design and approaches carried out at the level of horizontal synchronization. Determining Tokopedia's legal liability to users and the legal protection by parties engaged in electronic commerce is the aim of this study. Research findings show how consumers lack knowledge about their protection when making online purchases. Therefore, in the cases covered by these scripts, the buyer has little control and can only file a complaint through Tokopedia's electronic marketplace. In one of the cases covered in this script, a business actor acting as a seller has broken an agreement with a buyer. In fact, business actors acting in the capacity of the seller have acted in the scenario covered by this script against the interests of the buyer, or consumer, in electronic transactions